The Dynamic of Red Plate Bank's Financial Performance Before and During the Pandemic - Khavid Normasyhuri; Nuria Erisna; Panji Aji Setiawan (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2023)
The COVID-19 pandemic has disrupted business activities, including the banking industry. The Indonesian State Bank (BNI) might face the same challenges as other banks. However, as a well-established red plate bank, the dynamic of this bank needs to be further investigated to show how the pandemic affects its financial performance. The main objective of this study is to provide empirical evidence on whether the COVID-19 pandemic affects the financial performance of the red plate bank. In doing so,  the current researchers conducted a comparative analysis using paired sample t-tests. Time series data based on BNI's quarterly financial reports from the first quarter of 2017 to the fourth quarter of 2022  were collected through documentation. The data were partitioned into two groups, which were data before the pandemic and during the pandemic. The paired sample t-test results show that, in general, there is no statistical difference in BNI's financial performance before and during the pandemic. The finding confirmed that, as a red plate bank, BNI is a well-established bank with a sound financial state regardless of the pandemic.